Integrated delivery of family planning and childhood immunisation services: a mixed methods assessment of service responsiveness - Jessie K. Hamon; Misozi Kambanje; Shannon Pryor; Alice S. Kaponda; Erick Mwale; Helen E. D. Burchett; Susannah H. Mayhew; Jayne Webster (BMC, 2022)
Abstract Background Postpartum women represent a considerable share of the global unmet need for modern contraceptives. Evidence suggests that the integration of family planning (FP) with childhood immunisation services could help reduce this unmet need by providing repeat opportunities for timely contact with FP services. However, little is known about the clients' experiences of FP services that are integrated with childhood immunisations, despite being crucial to contraceptive uptake and repeat service utilisation. Methods The responsiveness of FP services that were integrated with childhood immunisations in Malawi was assessed using cross-sectional convergent mixed methods. Exit interviews with clients (n=146) and audits (n=15) were conducted in routine outreach clinics. Responsiveness scores across eight domains were determined according to the proportion of clients who rated each domain positively. Text summary analyses of qualitative data from cognitive interviewing probes were also conducted to explain responsiveness scores. Additionally, Spearman rank correlation and Pearson's chi-squared test were used to identify correlations between domain ratings and to examine associations between domain ratings and client, service and clinic characteristics. Results Responsiveness scores varied across domains: dignity (97.9%); service continuity (90.9%); communication (88.7%); ease of access (77.2%); counselling (66.4%); confidentiality (62.0%); environment (53.9%) and choice of provider (28.4%). Despite some low performing domains, 98.6% of clients said they would recommend the clinic to a friend or family member interested in FP. The choice of provider, communication, confidentiality and counselling ratings were positively associated with clients' exclusive use of one clinic for FP services. Also, the organisation of services in the clinics and the providers' individual behaviours were found to be critical to service responsiveness. Conclusions This study establishes that in routine outreach clinics, FP services can be responsive when integrated with childhood immunisations, particularly in terms of the dignity and service continuity afforded to clients, though less so in terms of the choice of provider, environment, and confidentiality experienced. Additionally, it demonstrates the value of combining cognitive interviewing techniques with Likert questions to assess service responsiveness.